Suppression of AMF accelerates N2O emission by altering soil bacterial community and genes abundance under varied precipitation conditions in a semiarid grassland - Li, Junqin; Meng, Bo; Yang, Xuechen; Cui, Nan; Zhao, Tianhang; Chai, Hua; Zhang, Tao; Sun, Wei (Frontiers in Microbiology, 2022)
Nitrous oxide (N2O) is one of the most important greenhouse gases contributing to global climate warming. Recently studies have shown that arbuscular mycorrhizal fungi (AMF) could reduce N2O emissions in terrestrial ecosystems, however, the microbial mechanisms of how AMF reduces N2O emissions under climate change are still not well understood. We tested the influence of AMF on N2O emissions by setting up a gradient of precipitation intensity (+50%, +30%, ambient (0%), -30%, -50%, and -70%) and manipulating the presence or exclusion of AMF hyphae in a semiarid grassland located in northeast China. Our results showed that N2O fluxes dramatically declined with the decrease of precipitation gradient during the peak growing season (June-August) in both 2019 and 2020. There was a significantly positive correlation between soil water content and N2O fluxes. Interestingly, N2O fluxes significantly decreased when AMF were present compared to when they were absent under all precipitation conditions. The contribution of AMF to mitigate N2O emission increased gradually with decreasing precipitation magnitudes, but no contribution in the severe drought (-70%). AMF significantly reduced the soil’s available nitrogen concentration, and altered the composition of the soil bacteria community including those associated with N2O production. Hyphal length density was negatively correlated with the copy numbers of key genes for N2O production (nirK and nirS) and positively correlated with the copy numbers of key genes for N2O consumption (nosZ). Our results highlight that AMF would reduce the soil N2O emission under precipitation variability in a temperate grassland except for extreme drought.